Design and Control of Alkali-Catalyzed Transesterification Reactors - Lersbamrungsuk, Veerayut; Srinophakun, Thongchai (ASEAN Journal of Chemical Engineering, 2013)
Controllability analysis during the design stage is needed to ensure that the plant can be operated properly. This research focuses on design and control of transesterification reactor. Effects of important design parameters including residence time, methanol/oil molar ratio, and reactor temperature to design conversion and controllability of the reactor are studied. Controllability is analyzed using linear system theory based on poles, zeros, and gains. The result reveals that for a given design conversion, the operation with high reactor temperature and low methanol/oil molar ratio is preferred.